The impact of perceived value on brand image and loyalty: a study of healthy food brands in emerging markets - García-Salirrosas, Elizabeth Emperatriz; Escobar-Farfán, Manuel; Esponda-Perez, Jorge Alberto; Millones-Liza, Dany Yudet; Villar-Guevara, Miluska; Haro-Zea, Karla Liliana; Gallardo-Canales, Rodrigo (Frontiers in Nutrition, 2024)
Introduction: Food brands that promote a healthy lifestyle are gaining more followers. Healthy food consumers are a conscious and demanding segment that values the quality and benefits they receive from a product and the ethical, environmental, and social impact of their purchasing decisions. The objective of the research is to evaluate the influence of perceived value components on health food brand image and brand loyalty in an emerging market.Methods: A cross-sectional and explanatory study was conducted considering 612 consumers of a healthy brand in Peru. The participants included women (65.2%) and men (34.8%), with ages between 18 and 56 (M= 22.56; SD= 5.95). Data were collected using a self-report form and statistically analyzed using PLS-SEM.The study hypotheses confirmed the impact of perceived emotional value, perceived social value, perceived financial value, and perceived quality on brand image and loyalty. However, the proposed model observes that perceived social value has no impact on brand loyalty.Implementing strategies that help build stronger, healthy brands is part of effective management for business leaders. In this context, the findings indicate that brands should effectively communicate their attributes and offer them that meet and exceed consumer expectations to achieve consumer loyalty. This is a mechanism to consolidate a strong and positive image that facilitates This is a provisional file, not the final typographic article.customer loyalty based on perceived value. The results obtained can help marketers and decisionmakers in the healthy food industry to design more effective brand strategies, which could increase demand for their healthy products.